Biogas Production by Anaerobic Co-Digestion Process between Community Distillery Slop with Glycerol Waste - Panpong, Kiattisak; Srimachai, Tussanee (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 4 (2018): October-December 2018, 2018)
This research aimed to increase the efficiency of biogas production from the community distillery slop (CDS) and the glycerol waste (GW) through the anaerobic co-digestion process. The feasibility study of using GW together with the CDS as co-substrate was tested by the bio-methane potential (BMP) in which different concentrations of GW ranging from 1-5% (v/v) were employed. The findings revealed that an anaerobic co-digestion process of the GW at 5% (v/v) concentration and the CDS were potentially improved both in terms of quality and quantity of biogas production. The experiment could produce maximum methane and methane production up to 2,245 mLCH 4 and 706 mLCH 4 /g VS respectively, which increased around 300%, higher than the only CDS single-digestion. The methane yield was well predicted by the Modified Gompertz Model compared with the data obtained from the experiments. This could be seen from the statistical regression coefficient values which higher than 95% (R 2 > 0.95). The obtained data which predicted by the Modified Gompertz Model would be used to design the continuous system in the next step. Keywords: Biogas production, Community Distillery Slop, Co-digestion, Glycerol waste